Additive-Induced Polymorphism of a Model Amino Acid Crystal - Khuu, Quang Chau; Le, Phi Dinh; Luu, Loc Cam; Trinh, Huyen Thi Thanh; Wolf, Stephan; Nguyen, Tuan Anh (Korean Journal of Chemical Engineering, 2024)
Additives have a multifaceted impact on nucleation and crystal growth mechanisms, which still require further charting. This contribution maps out the influence of a typical organic amino acid additive, L-phenylalanine, on the crystallization of a model amino acid, L-glutamic acid. The nucleation and growth processes are strongly modulated under the effect of this additive, which ultimately significantly influences polymorphic selection, phase transformation, shape, size, and size distribution of the crystalline products. A mixture of α-glu and β-glu nuclei is formed at low additive concentrations, while only α-glu nuclei are found at high additive concentrations. Thus, this additive molecule preferably induced α-glu conformation, thereby triggering the nucleation of α-glu instead of β-glu, which resulted in polymorphic selection of α-glu. Moreover, this additive favorably adsorbs on the facets of α-glu crystals, thereby inhibiting heterogeneous nucleation of β-glu, resulting in impeding a critical phase transformation pathway of α-glu to β-glu. This additive also remarkably impacted crystalline products’ shape, size, and size distribution.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Crystal growth; Nucleation; Phase transformation; Polymorphism